2008
DOI: 10.1007/s10875-008-9219-y
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Characterisation of the Hyper Immunoglobulin M Syndrome Associated with Congenital Rubella Infection

Abstract: The detection of cell-surface IgG but lack of serum IgG indicated that he may have an antibody secretion defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 22 publications
(27 reference statements)
2
17
1
Order By: Relevance
“…As predicted by our previous studies, we have confirmed the presence of germinal centres and isotype switched B lymphocytes in rHIM [12].…”
Section: Introductionsupporting
confidence: 91%
See 4 more Smart Citations
“…As predicted by our previous studies, we have confirmed the presence of germinal centres and isotype switched B lymphocytes in rHIM [12].…”
Section: Introductionsupporting
confidence: 91%
“…High-resolution CT scans of the thorax have not shown bronchiectasis. As previously noted, he has normal CD40 ligand expression (11.5 % CD3+ CD40L+cells on PMA/Calcium ionophore activation) [12] and normal sequence compared with a patient with XHIM [12,14,15]. He has wild type sequence for the UNG, CD40 and AICDA genes [12].…”
Section: Patient History and Previous Findingsmentioning
confidence: 83%
See 3 more Smart Citations